PENGEMBANGAN E-MODUL (BAHAN AJAR) MENGGUNAKAN CANVA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SEKOLAH DASAR - Azizah, Silvia; Muhammadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of use of technology in the production of teaching materials in schools. Even though there are adequate facilities for making teaching materials using technology. The reason teachers do not make the most of the existing facilities is because of a lack of time and not enough ability to design teaching materials using technology. This research aims to develop a valid, practical and effective e-module using canva in Indonesian language learning in grade IV of elementary school. This type of research uses a type of development research. The development model used is the ADDIE model which consists of five stages, namely Analyze, Design, Development, Implementation, Evaluation. The e-modules that have been designed are then validated by validators of material experts, linguists, media experts, and driving teachers using validation sheets in the form of questionnaires. The practicality of the product is carried out by filling out a questionnaire of teacher and student responses. The effectiveness test was carried out by giving pre-test and post-test questions to students. The results of this research obtained e-modules that are valid, practical, and effective to be used in the learning process. The validation results of four validators, namely material experts, linguists, media experts, and driving teachers, obtained a final result of 93% with the category "Very Valid". The practicality results of the questionnaire responses of teachers and students in the test school were 90.55% while in the school where the research was conducted obtained the final result of 94.52% with the category "Very Practical". The effectiveness results showed an increase in pre-test and post-test results. It can be concluded that the use of "E-Module (Teaching Materials) Using Canva in Indonesian Language Learning in Grade IV Elementary School" has proven to be valid, practical, and effective for use in the learning process.